Biomechanical evaluation of a novel biomimetic artificial intervertebral disc in canine cervical cadaveric spines - Celien A. M. Jacobs; Remco J. P. Doodkorte; S. Amir Kamali; Abdelrahman M. Abdelgawad; Samaneh Ghazanfari; Stefan Jockenhoevel; J. J. Chris Arts; Marianna A. Tryfonidou; Björn P. Meij; Keita Ito (JOR Spine, 2023)
Abstract Background Context Cervical disc replacement (CDR) aims to restore motion of the treated level to reduce the risk of adjacent segment disease (ASD) compared with spinal fusion. However, first‐generation articulating devices are unable to mimic the complex deformation kinematics of a natural disc. Thus, a biomimetic artificial intervertebral CDR (bioAID), containing a hydroxyethylmethacrylate (HEMA)—sodium methacrylate (NaMA) hydrogel core representing the nucleus pulposus, an ultra‐high‐molecular‐weight‐polyethylene fiber jacket as annulus fibrosus, and titanium endplates with pins for primary mechanical fixation, was developed. Purpose To assess the initial biomechanical effect of the bioAID on the kinematic behavior of the canine spine, an ex vivo biomechanical study in 6‐degrees‐of‐freedom was performed. Study Design A canine cadaveric biomechanical study. Methods Six cadaveric canine specimens (C3‐C6) were tested in flexion‐extension (FE), lateral bending (LB) axial rotation (AR) using a spine tester in three conditions: intact, after C4‐C5 disc replacement with bioAID, and after C4‐C5 interbody fusion. A hybrid protocol was used where first the intact spines were subjected to a pure moment of ±1 Nm, whereafter the treated spines were subjected to the full range of motion (ROM) of the intact condition. 3D segmental motions at all levels were measured while recording the reaction torsion. Biomechanical parameters studied included ROM, neutral zone (NZ), and intradiscal pressure (IDP) at the adjacent cranial level (C3‐C4). Results The bioAID retained the sigmoid shape of the moment‐rotation curves with a NZ similar to the intact condition in LB and FE. Additionally, the normalized ROMs at the bioAID‐treated level were statistically equivalent to intact during FE and AR while slightly decreased in LB. At the two adjacent levels, ROMs showed similar values for the intact compared to the bioAID for FE and AR and an increase in LB. In contrast, levels adjacent to the fused segment showed an increased motion in FE and LB as compensation for the loss of motion at the treated level. The IDP at the adjacent C3‐C4 level after implantation of bioAID was close to intact values. After fusion, increased IDP was found compared with intact but did not reach statistical significance. Conclusion This study indicates that the bioAID can mimic the kinematic behavior of the replaced intervertebral disc and preserves that for the adjacent levels better than fusion. As a result, CDR using the novel bioAID is a promising alternative treatment for replacing severely degenerated intervertebral discs.